2007
DOI: 10.1111/j.1471-4159.2007.04509.x
|View full text |Cite
|
Sign up to set email alerts
|

Gap‐junction blocker carbenoxolone differentially enhances NMDA‐induced cell death in hippocampal neurons and astrocytes in co‐culture

Abstract: The beneficial or detrimental role of gap junction communication in the pathophysiology of brain injury is still controversial. We used co-cultures of hippocampal astrocytes and neurons, where we identified homocellular astrocyte-astrocyte and heterocellular astrocyte-neuron coupling by fluorescence recovery after photobleaching, which was decreased by the gap junction blocker carbenoxolone (CBX). In these cultures, we determined the cell type-specific effects of CBX on the excitotoxic damage caused by N-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 62 publications
(126 reference statements)
2
24
1
Order By: Relevance
“…Like connexins, Panx1 and P2X7R contribute to Ca 2+ wave propagation by transfer of IP3 and ATP-induced ATP release independent of extracellular Ca 2+ (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Indeed, CBX accelerates NMDA-induced membrane depolarization with a concomitant rise in intracellular Ca 2+ in vitro (34). Although the high dosage of CBX was needed because of its partial exclusion by the blood-brain barrier (35,36), the present data also showed that CBX increased PILO-induced seizure susceptibility in WT mice.…”
Section: Discussionsupporting
confidence: 48%
“…Like connexins, Panx1 and P2X7R contribute to Ca 2+ wave propagation by transfer of IP3 and ATP-induced ATP release independent of extracellular Ca 2+ (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Indeed, CBX accelerates NMDA-induced membrane depolarization with a concomitant rise in intracellular Ca 2+ in vitro (34). Although the high dosage of CBX was needed because of its partial exclusion by the blood-brain barrier (35,36), the present data also showed that CBX increased PILO-induced seizure susceptibility in WT mice.…”
Section: Discussionsupporting
confidence: 48%
“…7). It is possible that CBX treatment increased the production of ROS [43], which induced phosphorylation of Cx43 and the subsequent inhibition of GJ through MAPK signaling [50]. Along the same line, ROS-induced DR5 upregulation most probably occurs through activation of c-Jun N-terminal kinase ( JNK) [51], which increased the expression of DR5 and the subsequent recruitment of Fas-associated death domain to form the DISC [52] and activation of downstream active caspases.…”
mentioning
confidence: 99%
“…Taken together, our results on the inhibition of dye transfer and downregulation of Cx43 in CBX-treated cells suggested that the enhancement in cell death observed upon treatment with CBX and TRAIL occurred through a GJ-dependent manner. However, it is difficult to rule out GJ-independent cell death because CBX was also shown to induce mitochondrial depolarization and oxidative stress through the production of reactive oxygen species (ROS) in neurons [43]. Generation of ROS subsequently activates mitogen-activated protein kinase (MAPK) and DR expression to initiate downstream death signals [44].…”
mentioning
confidence: 99%
“…This we have already seen for the analysis of the mitochondrial potential as a result of P2Y receptor activation in astrocytes and neurons and of gap junction inhibition in hippocampal mixed cultures (Zündorf et al, 2007).…”
Section: Discussionmentioning
confidence: 93%